2007
DOI: 10.1007/s00114-007-0279-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival in an extreme habitat: the roles of behaviour and energy limitation

Abstract: Extreme habitats challenge animals with highly adverse conditions, like extreme temperatures or toxic substances. In this paper, we report of a fish (Poecilia mexicana) inhabiting a limestone cave in Mexico. Several springs inside the cave are rich in toxic H 2 S. We demonstrate that a behavioural adaptation, aquatic surface respiration (ASR), allows for the survival of P. mexicana in this extreme, sulphidic habitat. Without the possibility to perform ASR, the survival rate of P. mexicana was low even at compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 26 publications
5
91
0
4
Order By: Relevance
“…Details on the study site can be found in Tobler et al (2006). To test for sex differences in the frequency of ASR, we reanalyzed data published in Plath et al (2007b). P. mexicana males (28.4±0.9 mm standard length, mean±SE) and females (36.0±1.9 mm) were exposed to both water from a sulfidic cave spring (83.6±28.1 μM H 2 S, 21.2±1.3% DO, n=12 measurements) and water from the same spring that was aerated for 1 h to remove H 2 S (0.8±1.2 μM H 2 S, 88.2±1.7% DO, n=3 measurements).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details on the study site can be found in Tobler et al (2006). To test for sex differences in the frequency of ASR, we reanalyzed data published in Plath et al (2007b). P. mexicana males (28.4±0.9 mm standard length, mean±SE) and females (36.0±1.9 mm) were exposed to both water from a sulfidic cave spring (83.6±28.1 μM H 2 S, 21.2±1.3% DO, n=12 measurements) and water from the same spring that was aerated for 1 h to remove H 2 S (0.8±1.2 μM H 2 S, 88.2±1.7% DO, n=3 measurements).…”
Section: Methodsmentioning
confidence: 99%
“…Sulfide detoxification in organisms capable of tolerating high and sustained concentrations of H 2 S is primarily achieved through its oxidation to less toxic sulfur species and subsequent excretion through the kidneys (Curtis et al 1972;Bagarinao 1992;Ip et al 2004). Due to the hypoxic conditions in sulfidic habitats, oxygen available for respiration is generally limited, but at the same time oxygen is also required for coping with the toxic effects of H 2 S. Experiments in the natural habitat indicate that P. mexicana males have a higher susceptibility to the adverse conditions than females (Plath et al 2007b). To survive in the hypoxic sulfidic environment, this species strongly relies on ASR (Plath et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, exposure to H 2 S has been shown to constrain energy acquisition in P. mexicana (Tobler et al 2009a). H 2 S causes and aggravates hypoxia in natural environments (Bagarinao 1992), driving exposed fish to trade off time between benthic foraging and aquatic surface respiration, which directly mediates survival in the toxic and hypoxic environment (Plath et al 2007b;Tobler et al 2009a). In addition, exposure to perpetually sulfidic environments requires active detoxification for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in tolerance likely arise from behavioural, morphological, and physiological modifications. Fish from sulphidic habitats readily engage in aquatic surface respiration upon exposure to H 2 S [125], and the ability to engage in this compensatory behaviour determines survivability in the natural environment [126]. In addition, sulphide spring fish are characterised by increases in gill surface area and head size, which improves oxygen acquisition efficiency [75,76].…”
Section: Adaptation To Sulphide Spring Environments In the Family Poementioning
confidence: 99%